Parity nonconservation effect in resonance recombination of polarized electrons with heavy hydrogen-like ions - Maiorova, Anaa V.; Shabaev, V. M.; Volotka, A. V.; Zaytsev, V. A.; Plunien, G.; Stöhlker, Thomas (Journal of physics. B, Atomic, molecular and optical physics, 2011)
Parity nonconservation (PNC) effect in recombination of a polarized electron with a heavy H-like ion in the case of resonance with a doubly excited state of the corresponding He-like ion is studied. It is assumed that photons of the energy corresponding to the one-photon decay of the doubly excited state into the 21S0 or 23P0 state are detected at a given angle with respect to the incident electron momentum. Calculations are performed for helium-like thorium (Z = 90) and gadolinium (Z = 64), where the 21S0 and 23P0 levels are near to cross and, therefore, the PNC effect is strongly enhanced.